A Case of Feeling of Cold on Legs Treated with Bee Venom and Scolopendrae Corpus Herbal Acupuncture - Lee Yoon-kyoung; Lim Seong-Chul; Jung Tae-young; Han Sang-won; Seo Jung-chul (Korean Pharmacopuncture Institute, 2005)
Objective : This study was designed to investigate the effect of bee venom and Scolopendrae Corpus herbal acupuncture on the feeling of cold on legs. Methods : The patient was managed by bee venom and Scolopendrae Corpus herbal acupuncture, body acupuncture and herbal medicine. The following points were selected : BL40, BL57, BL60; SP6. After bee venom and Scolopendrae Corpus herbal acupuncture treatment, body acupuncture was performed at the same points. We evaluated the patient through Visual Analogue Scale(VAS) and Digital Infrared Thermal Imaging(D.I.T.I). Results : After 12 times of treatment, the patient showed that clinical symptoms was decreased, VAS changed from 10 to 3 and there was also improvement change on D.I.T.I. Conclusions : According to the results, bee venom and Scolopendrae Corpus herbal acupuncture may have the effects on the feeling of cold on legs. But further studies and required to prove the effects of this methods.